Method to Elicit Local Wisdom in Perceiving the Transformation of Historical Living Environment - Anwar, Widya Fransiska F.; Said, Ismail; Ossen, Dilhsan R; Rasyidi, Muh. Hisyam (RUAS, 2012)
The study aim is to develop method of rebuilding identity study based by eliciting residents’ opinions on the historical riverside settlement in Palembang pertaining to the changing morphology of the city form. The objectives of this study include(1) literature review on analysis method on urban form transformationand people perception on urban and social transformation and (2) developing research method to the rebuilding identity study. This paper answers the question of what method can be used to analyze the identity of Palembang riverside settlement based on the change of locals’ perceptions on urban and social transformation. By comparing the previous studies on the aspects ofthe identity, the result shows thatby triangulating the previous method from urban morphology and people perception study is the proper method for rebuilding identity of riverside settlement. Paper concludes that the interdependency betweenurban morphology and people-place emotional bonding is a partof local wisdom that generates the identity of historical living environment.Keywords: morphology, emotional bonding, place identity, peopleperception